Position Sensitive Micro-Strip and Micro-Pixel Detectors - Pugatch, V.M. (Наука та інновації, 2012)
Physics and techniques of the metal foil detectors measuring and imaging charged particles and synchrotron radiation beams are presented. An extremely low thickness (~1 micron) of the Metal Micro-strip Detector (MMD) combined with its high radiation tolerance (~100 MGy) introduces an opportunity to keep a device in the beam, permanently. ‘In-situ’ operation of the MMD provides non-destructive beam diagnostics in real time. The applications of the micro-strip as well as micropixel detectors are briefly described.